The name of this band is r.e.m. eaudiobook A biography. - Carlin, Peter Ames (Books on Tape, 2024)
THE NEW YORK TIMES BOOK REVIEW EDITORS' CHOICE • An electrifying cultural biography of the greatest and last American rock band of the millennium, whose music ignited a generation—and reasserted the power of rock and roll "[Carlin's] unique gift for capturing the sweep and tenor of a cultural moment...is here on brilliant display." —Michael Chabon In the spring of 1980, an unexpected group of musical eccentrics came together to play their very first performance at a college party in Athens, Georgia. Within a few short years, they had taken over the world – with smash records like Out of Time , Automatic for the People , Monster and Green . Raw, outrageous, and expressive, R.E.M.’s distinctive musical flair was unmatched, and a string of mega-successes solidified them as generational spokesmen. In the tumultuous transition between the wide-open 80s and the anxiety of the early 90s, R.E.M. challenged the corporate and social order, chasing a vision and cultivating a magnetic, transgressive sound. In this rich, intimate biography, critically acclaimed author Peter Ames Carlin looks beyond the sex, drugs, and rock’n’roll to open a window into the fascinating lives of four college friends – Michael Stipe, Peter Buck, Mike Mills and Bill Berry – who stuck together at any cost, until the end. Deeply descriptive and remarkably poetic, steeped in 80s and 90s nostalgia, The Name of This Band is R.E.M. paints a cultural history of the commercial peak and near-total collapse of a great music era, and the story of the generation that came of age at the apotheosis of rock.